Pathomorphology, immunohistochemical, and molecular detection of an atypical porcine dermatitis and nephropathy syndrome (PDNS) due to PCV-2d-2 in naturally affected grower pigs of India. (October 2022) - Sahoo, Monalisa; Pathak, Mamta; Patel, Shailesh Kumar; Saikumar, G.; Upmanyu, Vikramaditya; Thakor, Jigarji Chaturji; Kumar, Pradeep; Singh, Rajendra; Singh, Karampal; sahoo, Nihar Ranjan
Abstract: Porcine circovirus type 2 (PCV-2) is of great economic significance to porcine industry worldwide. PCV-2 variants and genotypes, alternating world over, are the etiological agent of several clinical syndromes such as porcine dermatitis and nephropathy syndrome (PDNS), post-weaning multi-systemic wasting syndrome (PMWS) and others in pigs. This study is reporting an atypical manifestation of PDNS in twelve grower pigs, 3- to - 4.5 months age and either sex, died of the disease, with predominant lesions of nephropathy and no obvious clinical lesions in skin. Necropsy examination of pigs showed lesions of petechial -to- ecchymotic hemorrhages in the kidneys and in the right auricular musculature of the hearts. Microscopic lesions in H & E sections of the kidneys showed acute glomerulonephritis, interstitial nephritis, and vasculitis, but the skin morphology and architecture remained unaltered in contrast to the pathognomonic lesions of PDNS described in the literature. Other syndromic associations of PDNS in these cases included-perimyocarditis, interstitial pneumonia, depleted lymphoid tissues, tonsillitis, enteritis, and meningo-encephalitis. The lesional sites in duplicate paraffin tissue sections of kidneys, heart, lungs, spleen, lymph nodes, intestine, and brain demonstrated PCV-2 antigen in the cytoplasm of cells as highlighted by the intense immunolabeling on IHC staining. The PCV-2 positive organs reconfirmed by PCR, targeting ORF2 gene, which yielded 481bp size of products. The sequencing results of 481bp products on phylogenetic analysis showed 94% similarity with that of PCV-2 sequences in the database that grouped into PCV2d-2 genotype. The present report confirms, probably for the first time, the atypical PDNS cases due to PCV2d-2 genotype in naturally affected grower pigs of India. Highlights: The study describes the mortality in grower pigs due to an atypical form of porcine dermatitis and nephropathy syndrome (PDNS). Erythematous lesions of varying intensity were noted in kidneys and the heart, but not in the skin of the pigs. The microscopic lesions of diffuse, necrotizing granulomatous glomerulonephritis. and similar types of necrotizing inflammatory lesions in other organs were noted. Strong immunolabeling of PCV-2 antigen at the sites of histopathological lesions confirmed the association of PCV-2 with PDNS. Phylogenetic analysis revealed the PCV2d-2 genotype.